EDUCATION, CASTE AND OCCUPATIONAL DIFFERENTIALS IN FERTILITY IN INDIA - Kalyan SOM; Ramesh P. MISHRA (European Journal of Geography)
This study analyses the impact of four prominent factors (education, caste, occupation and development) on fertility in India. The study has also analysed the spatial variations of TFR in India. This spatial analysis also helps in identifying the impact of fertility on Development in India. Present study estimates fertility from census that covers all the reproductive age-women, and it does not allow any chance of sample error; this method has also adopted by UNFPA. Logistic regression analysis used to understand the impact of education, caste and occupation on fertility. Co-relation matrix and regression analysis used to determine the relation between TFR, IMR and Development. In India, West Bengal (2.41) state has the least fertility rate while Jammu and Kashmir (4.70) has highest one. Southern states have lower fertility along with Eastern states while North-east and central states have recorded high fertility. Women who have passed above secondary school of education give a prominent impact on fertility reduction in comparison to illiterate, primary and middle school passed. Marginal workers have very high fertility compare to main workers due to their feeling of insecurity in earnings and they increase number of child counted as gross family income.